Pelatihan Pemasaran untuk Meningkatkan Daya Saing UMKM Gig’s Batik di Yogyakarta - Harsoyo, Titik Desi; Kakanita Ari Puspitasari; Nala Tri Kusuma (LP3M Universitas Putra Bangsa, 2023)
The Community Service Program is implemented at Gig's Batik, one of the MSMEs which produce batik in Yogyakarta. It is located in Kwarasan Village RT 08 RW 06, Nogotirto Village, Gamping District, Sleman Regency, Special Region of Yogyakarta. As a batik producer, Gig's Batik faces fierce competition in the batik market, especially the domestic market. In order to compete in the increasingly stringent batik industry, Gig's Batik must always strive to improve its business practices. One of the crucial aspects in the success of batik MSMEs businesses is marketing. Meanwhile, in the marketing aspect, there are many activities or elements that companies can improve to increase its competitiveness. Based on the situation analysis, it was found that the main problems in the marketing function faced by Gig's Batik lie in unattractive product labels and limited mastery of technology applications. A company must pay attention to labels because of their role as a medium for information about products, companies and logos. In the era of digital marketing, MSMEs must have the skills to use the latest technology applications and utilize them to advance their business. To help partners solve their problems, the service team held training on labeling and the application named CapCut. Training was held in August-September 2023 at the Gig's Batik showroom. The outputs resulting from this activity are: (1) more informative and attractive new product labels, (2) videos created with the CapCut application and used as an online promotional tool on Gig's Batik's social media. The training is expected to increase Gigs's Batik knowledge and skills regarding product labels and mastery of technology applications that can support marketing activities, and in turn, increasing their competitiveness in batik market.